Boosting the hydrogen evolution performance of a ternary MoxCo1−xP nanowire array by tuning the Mo/Co ratio. Issue 24 (5th June 2019) - Zhang, Yintong; Wang, Zhiyuan; Du, Feng; He, Huichao; Alsaedi, Ahmed; Hayat, Tasawar; Li, Tao; Li, Guo-Ling; Zhou, Yong; Zou, Zhigang
Abstract : Volcano-like electrocatalytic HER activity of Mo x Co1− x P/CC due to the good balance of the double-sided effect. Abstract : It's imperative to develop efficient and low-cost non-noble metal electrocatalysts for the commercial application of the hydrogen evolution reaction under alkaline conditions. Herein, we prepared a series of vertical Mo x Co1− x P nanowire arrays on carbon cloth as an efficient HER catalyst. The electrocatalytic activity is strongly influenced by the Mo/Co ratio which is thought to be related to the changes in the electronic structure and the lattice structure due to the elemental substitution of Mo for Co. Density functional theory calculations reveal that the existence of Mo optimizes the free energy of hydrogen adsorption on the electrocatalyst surface. Meanwhile, the introduction of Mo damages the intrinsic crystal structure and generates a high density of lattice boundaries, which hinders the conductivity of the catalyst. Therefore, a typical volcano-like variation of the electrocatalytic activity was observed in Mo x Co1− x P with an increasing Mo/Co ratio. The catalyst (Mo0.25 Co0.75 P) with optimal Mo/Co = 0.25 : 0.75 exhibits outstanding HER performance. It requires an overpotential of 59 mV to achieve 10 mA cm −2 and possesses long-term durability for 50 hours in 1.0 M KOH. This study offers a promising low-cost catalyst for practical applications.